Quality of work life of paramedics practicing community paramedicine in northern Ontario, Canada: a mixed-methods sequential explanatory study - Behdin Nowrouzi-Kia; Jordan Nixon; Stephen Ritchie; Elizabeth Wenghofer; David VanderBurgh; Jill Sherman (James Cook University, 2021)
Introduction: This article aimed to evaluate pilot community paramedicine (CP) programs in northern Ontario from the perspectives of paramedics to gain program recommendations related to both rural and urban settings. Methods: An online questionnaire was created and distributed to 879 paramedics with and without CP experience employed at eight emergency medical services providers in northern Ontario. An explanatory sequential design was used to analyze and synthesize the results from the quantitative survey items and the open-ended responses. Results: Seventy-five (40.5%) respondents participated in a CP program, and the majority of 75 paramedics who indicated they participated in CP (n=41, 54.4%) were from rural areas. CP was generally well received by both paramedics currently practicing CP and those who were not practicing CP. The majority (86.3%) of paramedics stated paramedics should be practicing CP in the future. Paramedics identified developing professional relationships and improving health promotion as positive aspects of CP. Areas for CP program improvement included better organization and scheduling, improved training and a need for better patient tracking software. Conclusion: Engaging and consulting paramedics in the ongoing process of CP development and implementation is important to ensure they feel valued and are part of the change process.